THE GLOBAL RESEARCH MAPPING ON ENVIRONMENTAL AWARENESS IN EDUCATION: BIBLIOMETRIC ANALYSIS 2015-2025 - Vika Puji Cahyani; Munawwarah Munawwarah (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
Although many studies have discussed the relationship between education and environmental awareness, there are still some research gaps that need attention. For example, there is no comprehensive mapping that illustrates global research trends on environmental awareness in education. The urgency of this research lies in the attempt to address the gaps in academic literature, especially the lack of studies that systematically map global research trends on environmental awareness in education. This study aims to analyse global trends in research on environmental awareness in education based on scientific publications during the period 2015-2025. This study uses a bibliometric approach. Research data is collected from the main database, namely Scopus. There are inclusion and exclusion criteria in this study. Environmental awareness in education is closely related to various aspects, including attitudes, behaviour, and sustainability policies. There are 5 main topics related to environmental awareness, namely Environmental Awareness and Environmental Education, Sustainability and Sustainable Development, Consumer Environmental Awareness and Pro-Environmental Behaviour, Environmental Attitudes and Environmental Performance, Environmental Sustainability in Education. Improving environmental education is very important to prepare future generations who are more concerned about the environment and are ready to face the challenges of sustainability. Recommendations that can be applied in the context of education in Indonesia are the integration of environmental education in the curriculum, an experience-based learning approach, encouraging pro-environmental behaviour in society, collaboration with global institutions and the use of digital technology in environmental education.